Genotyping and Phylogenetic Position of Trichinella spiralis Isolates from Different Geographical Locations in China - Zhang, Xi; Han, Lu Lu; Hong, Xiu; Jiang, Peng; Niu, Yui Fei; Wang, Zhong Quan; Cui, Jing (Frontiers in Genetics, 2019)
In China, the nematode Trichinella spiralis is the main aetiological agent of human trichinellosis. We performed multi-locus microsatellite typing of T. spiralis isolates to improve the current knowledge of the evolution and population diversity. First, seven polymorphic microsatellite loci were used to infer the genetic diversity of T. spiralis collected in 10 endemic regions. Then, a Bayesian model-based STRUCTURE analysis, a clustering based on the Neighbor-Joining method and a principal coordinate analysis (PCA) were performed to identify the genetic structure. Finally, the phylogenetic position of Chinese isolates was explored based on 6 mitochondrial and nuclear genetic markers (cox1, cytb, 5S ISR, ESV, ITS1 and 18S rDNA) using the maximum likelihood and Bayesian methods. In addition, the divergence time was estimated with multiple genes using an uncorrelated log-normal relaxed molecular-clock model. A total of 16 alleles were detected in 2310 individuals (1650 muscle larvae and 660 adult worms) using 7 loci. The STRUCTURE analysis indicated that the T. spiralis isolates could be organized and derived from the admixture of two ancestral clusters, which was also substantiated through the clustering analysis based on the allelic data. PCA analysis separated most samples from Tiandong, Guangxi (GX-td) and Linzhi, Tibet (Tibet-lz) from the remaining isolates. However, both maximum likelihood and Bayesian inference supported the close relationship between Xiangfan, Hubei (HB-xf) and GX-td. The molecular dating analysis suggested that the Chinese isolates started to diverge during the late Pleistocene (0.69 Mya). Generally, T. spiralis was observed to harbour low genetic variation, and further investigation with deeper sampling is needed to elucidate the population structure.